Blow-up criterion for incompressible nematic type liquid crystal equations in three-dimensional space - Mahmood, Tariq; Shang, Zhaoyang (AIMS mathematics, 2020)
In this paper, we consider two incompressible nematic type liquid crystal models in threedimensional space. Blow-up criterions for weak and smooth solutions are established in homogenous and nonhomogenous Besov space with negative regular index, respectively. As a result, we improve some previous results in Besov space.